Relationship between Perceived Organizational Support and Organizational Citizenship Behavior for Wilayatul Hisbah Aceh Jaya Police Members - Nur Hasmalawati; Maulana, Samsoel; Vonna, Rizka Dara (Nosipakabelo: Jurnal Bimbingan dan Konseling Islam, 2025)
Members of the Wilayatul Hisbah Police have an important role in monitoring the implementation of Islamic Sharia, but the low OCB in some members means that the implementation of supervisory, coaching and law enforcement duties is not optimal. The aim of this research is to determine the relationship between the level of Perceived Organizational Support and Organizational Citizenship Behavior in Wilayatul Hisbah Aceh Jaya Police members. The research method used is quantitative research. The sample used was 114 members of Satpol PP and WH Aceh Jaya, using the total sampling technique. Retrieval of data using a questionnaire measured on a likert scale and distribution to the sample. The data analysis used is Pearson Product Moment. The research results show that Pearson Product Moment analysis between POS and OCB in Satpol PP and WH Aceh Jaya members shows a positive correlation with the Pearson correlation value of 0.601. Improvements in POS perception tend to be followed by improvements in OCB behavior. A significance value (p) of 0.001 smaller than 0.05 indicates that this relationship is significant.